Manajemen Kepemimpinan Kepala Sekolah Dalam Mendukung Implemetasi Kurikulum Merdeka Di Sekolah Pengerak - Ucu Diana Sari; Tri Widayatsih; Mahasir, Mahasir (J-CEKI : Jurnal Cendekia Ilmiah, 2025)
This study aims to describe the Principal's Leadership Management in supportingthe Implementation of the Merdeka Curriculum at SMA Negeri 1 Kayuagung. The research was conducted at SMA Negeri 1 Kayuagung using a qualitative method with a case study approach. The subjects of this study were the principal, deputy curriculum, and teacher educators. The stages of data collection were obtained by interview, observation and documentation. The results of this study are the Principal Leadership of SMA N 1 Kayuagung has done several things in planning the Merdeka Curriculum, including forming a core committee consisting of school leaders, teaching staff, and school committees; compiling ATP and teaching modules; planning a project to strengthen the Pancasila Profile; discussing student character development programs. The management of meaningful learning sequences is carried out in an organized and systematic manner, including scheduling teaching hours and teaching loads, forming a planned learning arrangement. The implementation of meaningful learning in SMA Negeri 1 Kayuagung can be categorized as successful. Meaningful learning activities such as project-based learning are able to raise the level of student enthusiasm for learning. Principal control is carried out every sixmonth period or at the end of the year.